Pectic polysaccharides from the infusions of P. tridentatum, F. angustifolia and M. suaveolens: structural characterization and modulation of the inflammatory activity - Martins, Vitor Manuel Ramalheira (2014)
In Trás-os-Montes region (Portugal), the small shrub (Pterospartum tridentatum), the narrow-leafed ash (Fraxinus angustifolia), and the apple mint (Mentha suaveolens) are vegetable species used in the preparation of infusions for medicinal purposes, such as protection against diabetes, hypertension, high levels of cholesterol and uric acid [1]. These infusions contain several types of polysaccharides, such as pectic polysaccharides and galactomannans (GM´s), often reported as immunomodulators [2, 3]. Pectic polysaccharides are structurally complex polymers, exhibiting different polymeric building blocks: homogalacturonans (HG), type I rhamnogalacturonans (RG-I), type II rhamnogalacturonans (RG-II) and xylogalacturonans (XG) [4]. The backbone of RG-I can be partly substituted with, among others, type-II arabinogalactans (AG-I ) that form ramified regions responsible for the modulation of the immune response [2]. For GM´s, factors like chain length, degree of branching and degree of acetylation seem to influence their immunomodulating activity [3].